How to Teach Arabic Writing Skills for IIUM Students - Yousif, Khalid Osman (s.n, 2012)
This research is descriptive and analytical, aim to analyze the linguistic errors of the sample students who are studying Arabic in the level of skill in the writing center for foundation in International Islamic University in Malaysia. We took into account the process of error analysis to determine the errors written for students of the sample in the expressions, written description and statement of reasons. We took into account also the duplicates of these errors and to learn counting numbers and proportions, and the subsequent perception shows how to solve this problem.